If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -8 = 4x Reorder the terms: -8 + y = 4x Solving -8 + y = 4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + y = 8 + 4x Combine like terms: -8 + 8 = 0 0 + y = 8 + 4x y = 8 + 4x Simplifying y = 8 + 4x
| a^3+b^2=72 | | y=(3m+2n)(6m-8n) | | 2.3x-0.4=15.7 | | (3x)x=48 | | X*-6x+5=0 | | -68=-5x-8 | | x^2+v^2=y | | 5=25t+10 | | 21=-9 | | 21=9 | | 5y+x=w | | y=-sin(3.14x+1)-2 | | -4+8V=6+3v | | X^2(x-3)=320 | | y=(5x-3)(2x+1) | | -6(4d+10)+7d=-3d | | 202=(4x-1)*(5x+3) | | 3(n-3)-(7-n)= | | 50.4=2.5x*(15.4+y) | | 12=7t-44 | | x+2/8=-3 | | 50.4=2.5x*(15.4+x)y | | 2y+3(y+5)= | | 50.4=2.5x*(15.4+x) | | 3x+1-2x-7=0 | | f(x)=2x^4+x^3-53x^2-14x+20 | | 10x-12=9x | | 12*k-13=39 | | 2-y=2-1 | | -5(-5+4w)=-15 | | 1=7t+8 | | 15+4k=-57 |